"Pickles Method" Inspired Tomato Derived Hierarchical Porous Carbon for High-Performance and Safer Capacitive Output. Issue 5 (6th April 2018) - Wang, Chao; Xiong, Ye; Wang, Hanwei; Yang, Ning; Jin, Chunde; Sun, Qingfeng
Abstract : Biomass derived porous carbon have attracted more and more attention for the application of energy storage. More effective activation strategy is required for production of biomass derived porous carbon. In this work, "pickle method" inspires the incorporated strategy of the activation agent, because it can realize more effective and uniform mixture between activation agent and precursor. Based on the cell structure, the tomato pickled with ZnCl2 is transferred into natural nitrogen doped (1.2%) porous carbon materials using the one-step annealing. Porous analysis based on density functional theory (DFT) confirms that the materials possess well-defined distributions of mesopores and micropores and high specific surface area (863.6 m 2 g −1 ). The synergetic effects of the hierarchical porous monolithic structure, natural nitrogen doping and high specific area results in the high specific capacitance (347.4 F g −1 at 0.5 A g −1 ). The ultimate symmetric supercapacitor exhibits ultrahigh specific energy density (142.6 Wh Kg −1 ) based on the active materials mass. Meanwhile, the materials exhibit less impurities (such as the oxygen of ultralow content (1.1%)), which benefits safer energy storage. Finally, drop, bending and nondestructive temperature tests demonstrate the stable and safe capacitive performance of the supercapacitors.